BLACK TURMERIC DATABASE: A DATABASE OF NATURAL COMPOUNDS FROM CURCUMA CAESIA ROXB. - KS, Mukunthan; B, Balaji; TN, PATEL (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Most species have their trademark metabolites or a class of chemicals that are generally disseminated inside the genus variety. Secondary metabolites from the black turmeric are predominantly camphor, terpenes, lactones, alkaloids, and phenols classification. A database was constructed with the predicted absorption, distribution, metabolism, elimination, and toxicity, druglikeliness, and physiochemical properties of the exclusive black turmeric 103 compounds. Â Methods: The interface has been designed using Microsoft Structured Query Language platform, keeping in mind the ease of use for a researcher. To support this, the entire set of chemicals and their properties was uploaded in database. Database is used as it is very efficient and supports multiple users at the same time. Results: Black turmeric database gives complete data of compounds by means of 4 segments. Physiochemical, pharmacodynamics, pharmacokinetics, druglikeliness, and molecular information are displayed with chemical structure. Conclusion: We solidly believe that the information from this database are the sources to infer novel pharmaceutical chemical compounds for medication.